Anatomical and pathological findings in hearts from fetuses and infants with cardiac manifestations of neonatal lupus - Llanos, Carolina (Oxford University Press, 2012)
Objective. The autopsy and clinical information on children dying with anti-SSA/Ro-associated cardiac manifestations of neonatal lupus (cardiac NL) were examined to identify patterns of disease, gain insight into pathogenesis and enhance the search for biomarkers and preventive therapies. Methods. A retrospective analysis evaluating reports from 18 autopsies of cardiac NL cases and clinical data from the Research Registry for Neonatal Lupus was performed. Results. Of the 18 cases with autopsies, 15 had advanced heart block, including 3 who died in the second trimester, 9 in the third trimester and 3 post-natally. Three others died of cardiomyopathy without advanced block, including two dying pre-natally and one after birth. Pathological findings included fibrosis/calcification of the atrioventricular (AV) node, sinoatrial (SA) node and bundle of His, endocardial fibroelastosis (EFE), papillary muscle fibrosis, valvular disease, calcification of the atrial septum and mononuclear pancarditis. There was no association of pathology with the timing of death except that in the third-trimester deaths more valvular disease and/or extensive conduction system abnormalities were observed. Clinical rhythm did not always correlate with pathology of the conduction system, and the pre-mortem echocardiograms did not consistently detect the extent of pathology. Conclusion. Fibrosis of the AV node/distal conduction system is the most characteristic histopathological finding. Fibrosis of the SA node and bundle of His, EFE and valve damage are also part of the anti-Ro spectrum of injury. Discordance between echocardiograms and pathology findings should prompt the search for more sensitive methods to accurately study the phenotype of antibody damage.